Telehealth for patients with interstitial lung diseases (ILD): results of an international survey of clinicians - John R Hurst; Joanna Porter; Anne-Marie Russell; Jaber S Alqahtani; Malik Althobiani (BMJ Open Respiratory Research)
Introduction Clinicians and policymakers are promoting widespread use of home technology including spirometry to detect disease progression for patients with interstitial lung disease (ILD); the COVID-19 pandemic has accelerated this. Data collating clinicians’ views on the potential utility of telehealth in ILD are limited.Aim This survey investigated clinicians’ opinions about contemporary methods and practices used to monitor disease progression in patients with ILD using telehealth.Methods Clinicians were invited to participate in a cross-sectional survey (SurveyMonkey) of 13 questions designed by an expert panel. Telehealth was defined as home monitoring of symptoms and physiological parameters with regular automatic transmission of data from the patient’s home to the clinician. Data are presented as percentages of respondents.Results A total of 207 clinicians from 23 countries participated in the survey. A minority (81, 39%) reported using telehealth. 50% (n=41) of these respondents completed a further question about the effectiveness of telehealth. A majority of respondents (32, 70%) rated it to be quite or more effective than face-to-face visit. There were a greater number of respondents using telehealth from Europe (94, 45%) than Asia (51, 25%) and America (24%). Clinicians reported the most useful telehealth monitoring technologies as smartphone apps (59%) and wearable sensors (30%). Telehealth was most frequently used for monitoring disease progression (70%), quality of life (63%), medication use (63%) and reducing the need for in-person visits (63%). Clinicians most often monitored symptoms (93%), oxygen saturation (74%) and physical activity (72%). The equipment perceived to be most effective were spirometers (43%) and pulse oximeters (33%). The primary barriers to clinicians’ participation in telehealth were organisational structure (80%), technical challenges (63%) and lack of time and/or workload (63%). Clinicians considered patients’ barriers to participation might include lack of awareness (76%), lack of knowledge using smartphones (60%) and lack of confidence in telehealth (56%).Conclusion The ILD clinicians completing this survey who used telehealth to monitor patients (n=81) supported its’ clinical utility. Our findings emphasise the need for robust research in telehealth as a mode for the delivery of cost-effective healthcare services in ILD and highlight the need to assess patients’ perspectives to improve telehealth utility in patients with ILD.